2005
DOI: 10.1258/0022215054798032
|View full text |Cite
|
Sign up to set email alerts
|

Epistaxis: Are temperature and seasonal variations true factors in incidence?

Abstract: To our knowledge, this is the largest study to date examining ambient temperature association and epistaxis, and the first to investigate presentation rate in place of admission rate. We feel that the exclusion of all patients with epistaxis not admitted to hospital introduces a bias. In this series, there is no correlation between ambient temperature, seasonal preponderance, presentation rate or admission rate for patients with epistaxis. This is contrary to previously reported findings. We do not support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 4 publications
6
54
0
3
Order By: Relevance
“…Although it can be suggested that epistaxis occurs more frequently in the dry and cold months, some studies question this paradigm. 21,22 Our numbers show a clear cumulation of cases in winter and spring, with a significant difference from European summer months. This is most probably caused by dry air conditions in the colder months.…”
Section: Discussionmentioning
confidence: 65%
“…Although it can be suggested that epistaxis occurs more frequently in the dry and cold months, some studies question this paradigm. 21,22 Our numbers show a clear cumulation of cases in winter and spring, with a significant difference from European summer months. This is most probably caused by dry air conditions in the colder months.…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, in this study we found a significant association between age and readmissions; with higher rates in patients 76 years and older. The elderly may be susceptible to initial episodes of epistaxis due to diminished elasticity of their nasal vessels [13]. However, an association between age and recurrent epistaxis requiring an ED readmission has not been previously reported [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the relationship between season, temperature, humidity and the presentation of epistaxis. The majority of these studies have shown a correlation with case frequency and at least one of the above-mentioned meteorological factors, [1-8] but other studies have shown no relationship [9-11]. Despite numerous reports on this topic, no known studies have been performed in a location with temperature fluctuations as great as in Alberta, Canada.…”
Section: Introductionmentioning
confidence: 99%